Successful planned pregnancy through vitrified-warmed embryo transfer in a woman with chronic myeloid leukemia: case report and literature review - Toshifumi Takahashi (Mediterranean Journal of Hematology and Infectious Diseases)
A 35-year-old female patient with chronic myeloid leukemia wanted to have a child. She had been treated with imatinib and had achieved major molecular remission, after which imatinib was intentionally discontinued and interferon-α treatment was initiated. After three failed cycles of artificial insemination with her husband’s semen, the patient underwent treatment with assisted reproductive technology. After two cycles of in vitro fertilization, two embryos (8-cell stage and blastocyst) were cryopreserved. The patient again had elevated BCR/ABL mRNA levels; thus, infertility treatment was discontinued. After 18 months of dasatinib treatment, major molecular remission was observed and the patient underwent vitrified–warmed embryo transfer with a single blastocyst. Thereafter, she became pregnant. Discontinuation of tyrosine kinase inhibitors combined with the timely initiation of infertility treatments, including assisted reproductive technology, may be useful for treating women with CML who wish to become pregnant.